Postmodern myths - Fotopoulos, Takis (Universidad Nacional de Quilmes, 2003)
The aim of this paper is to propose a theoretical framework on postmodernism from the viewpoint of the Inclusive Democracy project. In the first part of the paper, the crucial issue will be examined whether there has really been a break with modernity, as postmodernists assume, in the political, economic, scientific and cultural spheres. In the second part, the post-modern theoretical paradigm and politics will be assessed and in the final part the Inclusive Democracy approach on the issues raised by postmodernists will be discussed. The conclusion drawn from this paper is that a new form of neoliberal modernity has emerged in the last quarter of a century or so rather than a new era of postmodernity.